Introduction to Molecular Magnetism. From Transition Metals to Lanthanides Von Cristiano Benelli und Dante Gatteschi. (8th January 2016) - McInnes, Eric J. L.
Abstract : Wiley‐VCH, Weinheim 2015. 520 S., geb., 99.00 €.—ISBN 978‐3527335404